Character Education Values on English Textbook for the Ninth Grade of Junior High School - Slamet Asari; Candra Hadi Asmara; Yusyril Ichza Mahendra (Jetlal, 2022)
The objective of this research is to describe character education values that integrated in the English textbooks entitled Think Globally Act Locally for ninth grade of Junior High School. Researcher used Qualitative and descriptive approach that also known as descriptive qualitative as the research design. Researcher uses student’s English textbook entitled Bahasa Inggris: Think Globally, Act Locally as the data source which expected has 18 educational values as mentioned in Presidential Decree No.87 of 2017 on Strengthening Character Education included: (1) religious, (2) honesty, (3) tolerance, (4) discipline, (5) hard-working, (6) creative, (7) independence, (8) democratic, (9)curiosity, (10) nationalism,(11) patriotism, (12)appreciation, (13) communicative and friendly, (14) peace-loving, (15) keen of reading, (16) environmental care, (17) social care (18) and responsibility. The study found only 12 of 18 values, they are religious, honesty, hardworking, creative, independent, curious, appreciative, friendly/communicative, keen of reading, environment care, social care, and responsible.